Social Network Analysis About Brand Awareness of Shopee Indonesia on Twitter - Sorta Yocevina Putri Rumapea; Camelia Pasandaran; Rismi Juliadi (Jurnal Komunikasi Profesional, 2022)
Brand recognition and brand memory are two crucial elements in brand awareness. Shopee Indonesia is one of the e-commerce in Indonesia, which is quite active on Twitter social media. This study analyzes social networks about brand awareness on Twitter through the hashtag #ShopeeID. In addition, I also want to enrich research on social network analysis in e-commerce in Indonesia. This study uses the concept of brand awareness, social media Twitter, and Social Network Analysis (SNA). The SNA research method uses the Netlytic and Gephi applications. Data collection was taken from 23-30 May 2022 for later analysis. The results showed that using hashtags in status uploads on social media could build brand awareness. The hashtag #ShopeeID can create consumer awareness of a brand as one of the e-commerce companies in Indonesia. This awareness is formed through the frequent and repeated use of hashtags by both Shopee and consumers. Shopee, a key player in disseminating information, uses Twitter as a medium to provide information through promos and giveaways. This research has implications for how e-commerce companies use hashtags in social media to create brand awareness. Businesses should pay more attention to using specific hashtags that reflect the brand than the business. When consumers can recognize a brand, that's where brand awareness is achieved.